Transmission of Public Sector Fiscal Policy on Intergenerational Vertical Mobility and Indonesia’s Human Capital Quality - Maya Kasmita; Nita Hasnita (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2026)
This research examines public sector fiscal transmission as a mechanism for addressing intergenerational poverty traps in Indonesia. Despite mandatory social spending, its effectiveness in promoting upward social mobility remains contested. This study empirically assesses the causal relationship between sectoral fiscal interventions particularly education and health expenditures and improvements in the Human Capital Index (HCI) and vertical mobility prospects. Using panel data estimation, the analysis covers 38 Indonesian provinces during the post-pandemic recovery period from 2021 to 2024. Data were obtained from the Ministry of Finance, the World Bank, and Statistics Indonesia (BPS), focusing on functional budget realization and quintile-based outcomes. The findings show that fiscal inputs positively affect human capital development but display diminishing marginal returns, with an R² of 0.684 indicating that administrative absorption often precedes qualitative improvement. Individuals in the lowest income deciles exhibit significantly lower mobility, suggesting that fiscal policy functions more as a redistributive safety net than a transformative instrument. Policy implications emphasize a shift from input-based allocation to results-based financing linked to learning and health outcomes, alongside the removal of non-financial barriers to enhance upward mobility for the bottom 20 percent. Future research should employ longitudinal micro-level data to assess long-term mobility effects.